Parameterization of electron attachment rate constants for impurities in LArTPC detectors. (1st November 2022) - Li, Y.; Bromberg, C.; Diwan, M.; Kettell, S.; Martynenko, S.; Qian, X.; Paolone, V.; Stewart, J.; Thorn, C.; Zhang, C.
Abstract: The ability of free electrons to drift long distances at high velocities in pure liquid argon under an applied electric field has been exploited for the past forty years to implement detectors with increasingly larger volumes for high energy physics research. The attachment of free electrons to impurities in the LAr is an important limit on the free instrumented volume of these extremely large detectors, and impurity concentrations as small as 100 ppt can reduce their resolution and efficiency. In this paper, we summarize the electron attachment rate constants as a function of the applied electric field, for common impurities in LArTPCs, obtained from data in the literature. We further provide analytical functions to parameterize the data, which are useful to compare with new measurements, to model and analyze the performance of existing detectors, and to predict the performance of new detectors.